Memorizing Al-Qur'an as Santri’s Spiritual Character of Street Children Islamic Boarding School Attamur Bandung Regency - Boy Arief Rochman; Siti Rosmayati; Arman Maulana; Ali Mu'min Budiman; Ayit Irfani (STAI AL-FALAH CICALENGKA, 2021)
In principle, qualitative data analysis was carried out simultaneously with the data collection process. The process of collecting data could be done in qualitative research through observation and documentation. The analysis techniques used include data reduction, data presentation, and drawing conclusions or verification. Conclusions that 1) Islam recommends for its adherents to seek knowledge, because with knowledge we can distinguish between truth and falsehood, between virtue and evil, between wrong and right, between guidance and misguidance, between good and bad, between beneficial and evil. which is harmful. And knowledge is to the human mind like light to the eye, without which the eye becomes blind. 2) Knowledge that is obligatory for every Muslim to know is the knowledge of religion. Regarding revelation in accordance with what is in the book of Allah and the sunnah of His Messenger and with the teachings of aqidah and sharia. One of the places to gain religious knowledge is in places of study such as in mosques, madrasah, Islamic boarding schools, or at house.Keywords: Education, Memorizing the Qur'an, Spiritual Character. AbstrakPada prinsipnya analisis data kulitatif dilakukan bersamaan dengan proses pengumpulan data. Proses pengumpulan data dapat dilakukan dalam penelitian kualitatif melalui observasi dan dokumentasi. Teknik analisis dilakukan dengan digunakan mencakup reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Kesimpulan bahwa 1) Islam menganjurkan bagi para penganutnya mencari ilmu, karena dengan ilmulah kita dapat membedakan antara haq dan bathil, antara kebajikan dan kejahatan, antara yang salah dari pada yang benar, antara hidayah dan sesat, antara baik dan jelek, antara yang bermanfaat dan yang mudharat. Dan ilmu itu bagi akal manusia umpama cahaya bagi mata, yang tanpa cahaya itu mata menjadi buta. 2) Ilmu yang wajib bagi setiap muslim mengetahuinya adalah ilmu mengenai keagamaan. Tentang wahyu sesuai dengan apa yang ada dalam kitab Allah dan sunnah Rasulnya dan dengan ajaran aqidah dan syariat. Salah satu tempat untuk menimba ilmu keagamaan adalah di tempat pengajian-pengajian seperti di masjid, madrasah, pesantren, atau di rumah.Kata kunci: Pendidikan, Menghafal Al-Qur’an, Karakter Spiritual.